Program Pengabdian Masyarakat Melalui Edukasi Dan Skrining Profil Lipid Serta Hubungannya Dengan Perlemakan Hati Pada Komunitas Lansia - Yohanes Firmansyah; Friliesa Averina; Louise Audrey (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
Fatty liver is a medical condition in which fat builds up in liver cells, which can develop into steatohepatitis, fibrosis, cirrhosis and liver cancer if not treated properly. Fatty liver in the elderly causes an increased risk of serious complications due to the high prevalence of metabolic risk factors such as hypertension, diabetes, hyperlipidemia and obesity which are more common in the elderly. The importance of education and understanding risk factors so that the elderly community can adopt a healthy lifestyle is the main focus of this community service activity. Through the Plan-Do-Check-Act (PDCA) method, initial assessment, education, implementation of healthy eating and exercise patterns, and evaluation of the effectiveness of the intervention are carried out. The results showed that the majority of elderly people had cholesterol levels and liver function within normal limits, although 9.7% had hypercholesterolemia and 43% had SGOT levels that were not optimal. Continuous education and support are key in preventing and managing fatty liver and dyslipidemia in the elderly, thereby improving their quality of life.